Faculty Modeling Co-Teaching and Collaboration Practices in General Education and Special Education Courses in Teacher Preparation Programmes - Leila Ansari Ricci; Joan C. Fingon (Athens Institute for Education and Research, 2017)
As increasing numbers of students enter K-12 schools with varied learning needs, one viable option to address their needs is through co-teaching or pairing of general and special education teachers in the same classroom to help all students learn. This paper describes one general and one special education professor's first time experience modeling collaboration and co-teaching practices in their respective graduate reading courses at a large, urban, public university in Southern California, USA. Graduate students from both classes observed co-teaching modeled by their professors and participated in workshop sessions including PowerPoint presentations, videos, and small group activities to promote students' understanding of collaboration and co-teaching skills. Students also developed a co-teaching lesson plan in collaboration between general and special education partners. Data sources included faculty ratings of co-teaching lesson plans, students' evaluations of workshops, and students' written reflections of their overall experience. Findings suggest that open communication, willingness to participate, being flexible, and faculty modeling co-teaching approaches were among the key factors for effective co-teaching and collaboration.